Diversidade de artrópodes em cultivo de morangueiro convencional associado ao cravo amarelo - Stein, Humberto Baungartem (2015)
The strawberry Fragaria x ananassa Duch. (Rosaceae) is a pseudofruit rich in vitamin C and largely appreciated by consumers for its flavour and aroma. Its cultivation constitutes an important economic factor for familiar agriculture, given that it demands high quantity of labour and offers high yield per area. However, the high incidence of pests in conventional production leads to the indiscriminate use of pesticides. In order to reduce such use, we propose the increase of natural enemies of conventional strawberry pests by means of habitat diversification with the attractive plant Tagetes erecta L.. The experiment was conducted in a strawberry cultivation in the municipality of Alfredo Vasconcelos, Minas Gerais, Brazil. We adopted two treatments, with three beds each: a) diversified treatment, in which strawberry cultivation was associated to yellow marigold T. erecta; b) monoculture treatment, with only conventional strawberry. We performed weekly samplings of arthropods, during six weeks, using beating against white tray and oral sucker on the strawberries and yellow marigold, in addition to Moericke adapted traps at plant height. The arthopofauna data were submitted to statistical and fauna analyses to compare the richness and abundance of pests and natural enemies in both monoculture and diversified environments. We also evaluated the potential of the yellow marigold as host plant for natural pests of strawberry. We verified that the diversification of strawberry cultivation with marigold lead to higher richness, abundance and diversity of natural enemies, such as non-pests phytophagous for the culture. As attractive plant for strawberry, yellow marigold increased the diversity of arthropods and natural enemies, as well as phytophagous species alternative to entomophagous in strawberry cultivation.